2003
DOI: 10.1023/a:1024934008982
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: An increase in the interaction between advanced glycation end-products (AGEs) and their receptor RAGE is believed to contribute to the pathogenesis of chronic complications of Diabetes mellitus, which can include bone alterations such as osteopenia. We have recently found that extracellular AGEs can directly regulate the growth and development of rat osteosarcoma UMR106 cells, and of mouse calvaria-derived MC3T3E1 osteoblasts throughout their successive developmental stages (proliferation, differentiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 27 publications
3
18
1
Order By: Relevance
“…7). It has been shown that AGEs themselves have the ability to stimulate RAGE expression in osteoblastic cells (27), as well as AGE-R3 (Galectin-3) expression (61). However, we could not see any change in the level of expression of AGE-R3 in RAW264.7 cells, probably due to cell-type specificity.…”
Section: Tablecontrasting
confidence: 76%
See 2 more Smart Citations
“…7). It has been shown that AGEs themselves have the ability to stimulate RAGE expression in osteoblastic cells (27), as well as AGE-R3 (Galectin-3) expression (61). However, we could not see any change in the level of expression of AGE-R3 in RAW264.7 cells, probably due to cell-type specificity.…”
Section: Tablecontrasting
confidence: 76%
“…AGE-modified collagen also interferes with integrinmediated osteoblastic attachment (26). RAGE has been shown to be expressed in osteoblasts (21,27) and may modulate AGEdependent signaling in osteoblasts (27). This observation could explain in part the decreased expression of transcription factors responsible for osteoblastic differentiation in type I diabetic mice model (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…AGEs accumulate in bone tissue during DM (Katayama et al 1996, Saito et al 2006 and may participate in the pathogenesis of DM-related osteoporosis. In support of this possibility, AGEs are capable of affecting bone cells directly since cultured osteoblastic cells (Cortizo et al 2003, Santana et al 2003 as well as bone tissue in vivo (Santana et al 2003) express receptor for AGEs (RAGE).…”
Section: Introductionmentioning
confidence: 99%
“…AGE receptors have been identified on various cell types including macrophages, endothelial cells [45], various renal cell types such as proximal tubular cells, mesangial cells and podocytes [46,47] nerve cells, muscle cells [48] and cells in the vasculature [12]. The AGE receptor system can be broadly divided into two arms: one is associated with increases in oxidative stress, growth, and inflammation probably best represented by RAGE [49,50], the other is involved in AGE detoxification and includes scavenger receptors such as CD36 (liver) as well as the AGE receptors AGE-R1 and AGE-R3 (via renal clearance).…”
Section: Ages As Ligands -Cellular Bindingmentioning
confidence: 99%